Decline of jackfruit (Artocarpus heterophyllus) incited by Phytophthora palmivora in Vietnam - TRI, Mai Van; VAN HOA, Nguyen; MINH CHAU, Nguyen; PANE, Antonella; FAEDDA, Roberto; DE PATRIZIO, Alessandro; SCHENA, Leonardo; OLSSON, Christer; WRIGHT, Sandra; RAMSTEDT, Mauritz; et al. (Phytopathologia Mediterranea, 2015)
A new disease of jackfruit (Artocarpus heterophyllus Lam.) was observed in the south- eastern region of South Vietnam. Symptoms included root rot, cankers and gummosis of trunks, chlorosis, wilt, blight of leaves, defoliation, fruit brown rot, and tree death. The disease was found in 10% of surveyed farms with an incidence varying from 2% to nearly 60% of the trees. A Phytophthora species, identified as P. palmivora (Butler) Butler, using the ITS1-5.8S-ITS2 region of the rDNA as a barcode gene and morphological and cultural features, was consistently isolated from symptomatic roots, fruits, trunk cankers and leaves. Koch’s postulates were fulfilled using pathogenicity tests on seedlings, leaves and detached fruits of jackfruit. To our knowledge, this is the first report of P. palmivora on jackfruit in Vietnam.